Qur'anic Moral Education for Addressing Students' Moral Degradation in the Digital Era: A Thematic Exegesis of Q. Luqman 31:12–19 - Dede Satria Putra; Ainur Rhain (Pustaka Peradaban, 2026)
Students' moral degradation in the digital era has become an increasingly urgent educational issue, characterized by declining civility, weakened respect for parents and teachers, cyberbullying, excessive dependence on digital media, and diminished self-control. Although previous studies have discussed Islamic education, character formation, and Qur'anic moral values, limited attention has been given to explaining how Qur'anic moral education functions as an integrated pedagogical framework for addressing these challenges. This study aims to analyze the concept of moral education in the Qur'an through a thematic exegetical (tafsīr mawḍūʿī) approach, identify the forms of students' moral degradation in the digital era, and formulate a Qur'anic moral education framework for contemporary character education. This library research employs thematic Qur'anic exegesis focusing on Q. 31:12–19, supported by classical and contemporary Qur'anic commentaries and relevant scholarly literature. The findings culminate in an integrated Qur'anic moral education framework comprising tawḥīd, adab, spiritual formation, social and communication ethics, and educational methods based on exemplary conduct, moral exhortation, habituation, and supervision. These elements constitute an integrated pedagogical framework that strengthens students' internal moral regulation through God-consciousness (murāqabah), self-regulation, and ethical digital communication. This study contributes to thematic Qur'anic exegesis and Islamic education by providing a conceptual framework for character formation that is both theoretically grounded and relevant to the moral challenges of the digital era. Degradasi moral peserta didik di era digital menjadi salah satu persoalan pendidikan yang semakin mendesak, ditandai dengan menurunnya kesantunan, berkurangnya penghormatan kepada orang tua dan guru, maraknya perundungan siber, ketergantungan berlebihan pada media digital, serta melemahnya pengendalian diri. Meskipun berbagai penelitian telah membahas pendidikan Islam, pembentukan karakter, dan nilai-nilai moral Al-Qur'an, masih terbatas kajian yang menjelaskan bagaimana pendidikan moral Qur'ani berfungsi sebagai kerangka pedagogis terpadu untuk menjawab tantangan tersebut. Penelitian ini bertujuan menganalisis konsep pendidikan moral dalam Al-Qur'an melalui pendekatan tafsir maudhu'i, mengidentifikasi bentuk-bentuk degradasi moral peserta didik di era digital, serta merumuskan kerangka pendidikan moral Qur'ani bagi pendidikan karakter kontemporer. Penelitian ini merupakan penelitian kepustakaan yang menggunakan metode tafsir maudhu'i dengan fokus pada QS. Luqman [31]:12–19, didukung oleh kitab-kitab tafsir klasik dan kontemporer serta berbagai literatur ilmiah yang relevan. Hasil penelitian menunjukkan bahwa pendidikan moral Qur'ani membentuk suatu kerangka pedagogis terpadu yang mencakup tauhid, adab kepada orang tua dan guru, pembinaan spiritual, etika sosial dan komunikasi, serta metode pendidikan melalui keteladanan, nasihat, pembiasaan, dan pengawasan. Kerangka tersebut memperkuat regulasi moral internal peserta didik melalui muraqabah, pengendalian diri, dan komunikasi digital yang beretika. Penelitian ini berkontribusi terhadap pengembangan kajian tafsir tematik dan pendidikan Islam dengan menawarkan kerangka konseptual pendidikan moral Qur'ani yang relevan bagi pembentukan karakter peserta didik di era digital.